2022
DOI: 10.18388/abp.2020_5809
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ERVK13-1 aggravates osteosarcoma through the involvement of microRNA-873-5p/KLF5 axis

Abstract: Objective: To explore the effect and mechanism of long noncoding RNA ERVK13-1 on osteosarcoma (OS) cell development by regulation of miR-873-5p/KLF5 axis. Methods: The expression of ERVK13-1 in the collected tissue was detected by RT-qPCR, and then the relationship between ERVK13-1 expression and clinical characteristics of OS patients was analyzed. After OS cell lines were transfected with miR-873-5p inhibitor, si-ERVK13-1, si-KLF5 or their negative controls, the expression of ERVK13-1, miR-873-5p, and KLF5 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…GLIDR is upregulated and promotes glioma [ 77 ], lung [ 78 ], and prostate [ 79 ] cancers by acting as competing endogenous RNAs for miRNAs. ERVK13-3 is upregulated in osteosarcoma [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…GLIDR is upregulated and promotes glioma [ 77 ], lung [ 78 ], and prostate [ 79 ] cancers by acting as competing endogenous RNAs for miRNAs. ERVK13-3 is upregulated in osteosarcoma [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of lncRNA on miRNA, we have also reported that sponging of miRNA-494 by HOXA11-AS enhances the expression of nicotinamide adenine dinucleotide (NAD)(P)H: quinone oxidoreductase 1 [13]. ERVK13-1 suppresses miR-873-5p by sponging it, promoting the expression of its target gene KLF5 and enhancing malignant phenotypes in osteosarcoma [21]. In our study, KLF5 expression was not altered by miR-873-5p mimics and inhibitors or ERVK13-1 knockdown in BUC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we examined the expression of three lncRNAs reported to regulate miR-873-5p, namely, ERVK13-1 [21], MALAT1 [22], and DDX11-AS1 [23,24]. The expression of ERVK13-1 was 5 times higher in T24 cells than in RT4 cells.…”
Section: Effects Of Altered Gnmt Expression On Tumor Growth and Metas...mentioning
confidence: 99%